An Intercultural Communication Training Test In A Special Case Of Europe (An Applied Field Study Through The Instrument Of Virtual Conduit) - Yagbasan, Mustafa; Argin, Emrah (Elsevier Science Bv, 2014)
In the social life, social behaviours can undoubtedly carry different features based upon such as genetic, hereditary and so on reasons. Theological, geographical, environmental factors and family environment can be shown as an example that affects the cultural-oriented indivudual learning process. For example, violence is a second learnt pattern of behavior and social environment can directly affect this learning process (living environment, family or local media, etc.) On the other hand it seems possible to say the same thing for many of the cultural achievements. Societies, even if they live on different regions can meet in virtual and real environment in case of 21st century conditions. Communicating obligation has emerged via social channels on todays global village with regarded as the enemy or other cultures until recent history. Therefore, recognizing each other's culture better (learning) and the digesting are important for a more livable world order because oriental and occidental trends have reached the condition of threatening the entire world. The main problem here is whether intercultural communication is possible with education or how to overcome a bias. European countries constitute the system of this study that reference to the basic hypothesis; in a globalized world conditions intercultural communication can be carried out on a virtual environment. MSN, Facebook, or Twitter as a media channels used in this study, a random sample (random) selected by the students studying in twenty European countries in the field of social sciences (communication and closeness with the demand) and tried to reach the questionnaire and were asked to answer the questions. In this study, it was tested that youngsters in European countries are positive or open to virtual friendship with the Turks and possibility of intercultural communication education through virtual channel. Important findings were concluded as a result of the study. (C) 2014 Published by Elsevier Ltd.
4th World Conference on Learning, Teaching and Educational Leadership (WCLTA) -- OCT 27-29, 2013 -- Univ Barcelona, Barcelona, SPAIN
Keywords: Remote Intercultural Communication; Intercultural Education; Intercultural Virtual Environment